McGraw-Hill encyclopedia of science and technology : an international reference work in fifteen volumes including index - Yelles, Marvin (New York : McGraw-Hill, 1960)
"This encyclopedia presents pertinent information in every area of modern science and technology. Although the third edition is considerably enlarged, by third edition considerably enlarged by about 1000 pages and 1,000,000 words, the organization follows the plan that was so successful in the two previous edition."
Includes bibliographies.
English text.
Keywords: Science -- Encyclopedias; Technology -- Encyclopedias